Exploring the utility of Deep Red Anthraquinone 5 for digital staining of ex vivo confocal micrographs of optically sectioned skin. Issue 4 (28th December 2020) - Ortner, Vinzent Kevin; Sahu, Aditi; Cordova, Miguel; Kose, Kivanc; Aleissa, Saud; Alessi‐Fox, Christi; Haedersdal, Merete; Rajadhyaksha, Milind; Rossi, Anthony Mario
Abstract: We investigated the utility of the fluorescent dye Deep Red Anthraquinone 5 (DRAQ5) for digital staining of optically sectioned skin in comparison to acridine orange (AO). Eight fresh‐frozen thawed Mohs discard tissue specimens were stained with AO and DRAQ5, and imaged using an ex vivo confocal microscope at three wavelengths (488 nm and 638 nm for fluorescence, 785 nm for reflectance). Images were overlaid (AO + Reflectance, DRAQ5 + Reflectance), digitally stained, and evaluated by three investigators for perceived image quality (PIQ) and histopathological feature identification. In addition to nuclear staining, AO seemed to stain dermal fibers in a subset of cases in digitally stained images, while DRAQ5 staining was more specific to nuclei. Blinded evaluation showed substantial agreement, favoring DRAQ5 for PIQ (82%, Cl 75%‐90%, Gwet's AC 0.74) and for visualization of histopathological features in (81%, Cl 73%‐89%, Gwet's AC 0.67), supporting its use in digital staining of multimodal confocal micrographs of skin. Abstract : Acridine orange has become a popular choice for clinical fluorescence imaging using ex vivo confocal microscopy (EVCM) of skin. To increase clinical utility and implementation, digital staining of combined fluorescence‐reflectance images can help increase the clinical utility and implementation of EVCM. This trial sought to investigate a new fluorophore for skin, DRAQ5, and compare it to the current gold standard, acridine orange, for digital staining of EVCM images. Blinded evaluation by three investigators showed a preference for DRAQ5.